No it is! - Kentridge, William, 1955-; Weltz, Betty; Breidbach, Angela; Reinhardt, Sophie, 1964-; Martin-Gropius-Bau (Berlin, Germany); Berliner Festspiele (Köln : Walther König, 2016)
'NO IT IS' is a catalogue of the exhibition at the Martin Gropius Bau in Berlin and the performances at the Berliner Festspiele in summer 2016. But it is also an artist's book incorporating a libretto for a performed guided tour of the exhibition: a performance which is both a guide to the exhibition and also an exhibit within the exhibition.
"Includes 18 augmented reality video fragments!"--Jacket.
Published on the occasion of 'NO IT IS! William Kentridge Exhibitions/Performances/Lectures' held at Martin-Gropius-Bau 12 May-21 August 2016 and Haus der Berliner Festspiele, Foreign Affairs - International Performing Arts Festival, 5-17 July 2016.
boek
Keywords: Kentridge, William, -- 1955- -- Exhibitions; Kentridge, William, -- 1955-; Art, South African -- 21st century -- Exhibitions; Art, South African -- 20th century -- Exhibitions; Art, South African; Kentridge, William -- 1955-; 1900-2099; Exhibition catalogs